Impact of maritime education on HRM: insights from STIP Jakarta graduates - Retno Sawitri Wulandari; Marudut Bernadtua Simanjuntak (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This research examines management practices in Marketing, Innovation, and Technology within Maritime Affairs, focusing on graduates of the Maritime Institute Jakarta (STIP Jakarta). By qualitatively analyzing the perspectives of 70 officers, including deck and engine officers and shipping professionals, the study reveals key insights. It highlights the importance of digital marketing, continuous improvement, and technology adoption in enhancing competitiveness and operational efficiency within the maritime industry. Furthermore, it emphasizes professionalism and adherence to international standards such as the IMO-STCW, demonstrating the industry's dedication to safety, competency, and regulatory compliance. The results emphasize the interdependence of effective management practices, regulatory adherence, and professional growth, providing practical insights for industry practitioners, policymakers, and training institutions to navigate maritime management complexities effectively.